Secondary abdominal pregnancy: a case report - Nagamuthu, Ezhil Arasi; Fatima, Syeda Sumaiya (International Journal of Research in Medical Sciences, 2017)
An ectopic pregnancy is a condition in which a fertilized egg settles and grows in any location other than the inner lining of the uterus. The vast majority of ectopic pregnancies is so-called tubal pregnancies and occurs in the Fallopian tube (98%); however, they can occur in other locations, such as the ovary, cervix, and abdominal cavity. Abdominal pregnancies represent just about 1% of ectopic pregnancies. The incidence of abdominal pregnancy ranges between 1:10000 pregnancies and 1:30000 pregnancies.Maternal mortality and morbidity are also very high especially if the condition is not diagnosed and managed appropriately. Abdominal pregnancy at term with a healthy viable fetus is therefore an extremely rare condition hence we present a case of abdominal pregnancy for publication.